Re-Design Klinik Bersalin “Bidan Jeanne” di Kota Depok Jawa Barat - Nindya Ayu Widyanugrah; Yusita Kusumarini; Anik Rakhmawati (Intra, 2018)
Maternity Clinic is a place that provides professional services related to pregnancy, ranging from control of uterus, childbirth, consultation, pregnancy exercise, to postpartum control. The design of maternity clinics with homey concept so that patients do not feel tense and feel comfortable. The maternity clinic "Midwife Jeanne" has not implemented the ideal design yet lacks a comfortable interior ambience, lack of concepts, ambience and good circulation despite having stood for 32 years. The formulation of the problem is how to design the interior of the maternity midwife clinics that can create space facilities that support the needs of patients from before delivery until after childbirth? The method used is the design stage design thinking, data collection methods, data processing methods, and methods of data analysis. Design thinking method using 7 stages of understanding, observe, point of view, ideate, prototype, test, Implement. The homey theme is expected to create a design atmosphere that supports the needs of patients before and after childbirth. The design of the maternity clinic is equipped with yoga facilities, salon, cafeteria, and breastfeeding room.